Clash of organisational cultures? A comparative analysis of American and British approaches to the coordination of defence, diplomacy and development in stability operations, 2001-2010 - Baumann, A (2012)
This thesis examines the challenge of coordinating civilian and military efforts within a so-called ‘whole-of-government’ approach to stability operations. The empirical analysis focuses on British and American attempts to implement an integrated civilian-military strategy in Afghanistan and Iraq between 2001 and 2010. Unlike many existing analyses, the thesis consciously avoids jumping to the search for solutions to fix the problem of coordination and instead offers a nuanced explanation of why it arises in the first instance. Empirical data was gathered through personal interviews with a wide range of civilian and military practitioners between 2007 and 2011. Together with the in-depth study of official documents released by, and on, the defence, diplomatic and development components of the British and American governments, they provide the basis for a fine-grained analysis of obstacles to interagency coordination. The thesis offers a framework for analysis that is grounded in organisation theory and distinguishes between material, bureaucratic and cultural dimensions of obstacles to interagency coordination. It identifies organisational cultures as a crucial force behind government agencies’ reluctance to participate and invest in an integrated approach. The empirical chapters cover interagency dynamics within the government bureaucracy and in operations on the ground, including the role of specialised coordination units and Provincial Reconstruction Teams in the pursuit of coordination. The thesis concludes that stabilisation remains an inherently contested endeavour for all organisations involved and that the roles and expectations implied by contemporary templates for coordination clash with prevailing organisational identities and self-perceptions. These findings caution against the procedural and technocratic approach to interagency coordination that permeates the existing literature on the subject and many proposals for reform. While the thesis examines a specific empirical context, its conclusions have broader implications for civilian-military coordination and the quest for an integrated approach to security in the twenty-first century.